Potential Mechanisms for the Ketamine-Induced Reduction of P3b Amplitudes - Rosburg, Timm; Schmidt, André (Frontiers in Behavioral Neuroscience, 2018)
Ketamine as N-methyl d-aspartate (NMDA) receptor antagonist can be used to model transient psychotic symptoms in healthy individuals. There are consistent reports that, aside from such psychotomimetic effects, the amplitude of the event-related potential (ERP) component P3b to targeted stimuli is diminished after ketamine administration. This P3b reduction could be directly related to the pharmacological properties of ketamine or, more indirectly, to its psychotomimetic effects, which may result in an increased difficulty to perform the task. In order to clarify this issue, the current review summarizes the effects of task difficulty on ERP components related to stimulus evaluation and context updating (P3a, P3b), as well as to sensory processing (P1, N1), and contrasts the effects of task difficulty with those of ketamine. The most important difference is that increased task difficulty leads to increased P3a amplitudes to distractors presented in same modality as targets, whereas ketamine leads to reduced P3a amplitudes for such distractors. This indicates that the decreased P3b amplitudes after ketamine cannot be explained by a drug-induced increased task difficulty. The conjoint reductions of P3a and P3b amplitudes instead suggest that working memory operations are impaired after ketamine, which is in line with previous behavioral findings.